2018
DOI: 10.1002/cnma.201700382
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Photoluminescence from Small Copper, Silver, and Gold Nanoparticles

Abstract: Here, we report the synthesis and near‐infrared photoluminescence properties of small‐diameter (∼2–3 nm) silver and copper nanoparticles. Periodic trends in nanoparticle quantum yields, observed lifetimes, and emission peak features are studied and compared to each other as well as to previously reported small diameter gold nanoparticles. These trends are distinct from optoelectronic features observed from either their cluster (4–100 atoms) or larger NP (diameter >5 nm) counterparts. Taken together, the succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…NIR PL was observed for each of the monometallic particle types, with element-specific differences in emission energy and quantum yield (Figure ). Interestingly, an excitation transition at ∼360 nm was observed for each metal core, consistent with ligand-to-metal charge transfer states that have been reported for luminescent coinage metal complexes , and emissive Au clusters, suggesting a surface chemistry-mediated mechanism for each coinage metal NP . Importantly, the CuNPs and AgNPs exhibit quantum yields that are on the same order of magnitude as those from AuNPs, illustrating their potential as complements to AuNPs in NIR-driven applications .…”
Section: Metallic Surface Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…NIR PL was observed for each of the monometallic particle types, with element-specific differences in emission energy and quantum yield (Figure ). Interestingly, an excitation transition at ∼360 nm was observed for each metal core, consistent with ligand-to-metal charge transfer states that have been reported for luminescent coinage metal complexes , and emissive Au clusters, suggesting a surface chemistry-mediated mechanism for each coinage metal NP . Importantly, the CuNPs and AgNPs exhibit quantum yields that are on the same order of magnitude as those from AuNPs, illustrating their potential as complements to AuNPs in NIR-driven applications .…”
Section: Metallic Surface Propertiessupporting
confidence: 80%
“…Near-infrared emission spectra of CuNPs, AgNPs, and AuNPs following excitation at 360 nm. Reprinted with permission from ref . Copyright 2018 John Wiley & Sons, Inc.…”
Section: Metallic Surface Propertiesmentioning
confidence: 99%
“…Photoluminescence spectra of Cu NPs bio-synthesized using Gum Kondagogu extract showed an emission peak at 430 nm when illuminated at 325 nm [143]. Cu NPs PL revealed an emission band in the near-infrared region at 816 nm with photoexcitation with UV-vis light at 360 nm [144]. The collected data revealed that the PL emission of Cu NPs not only depends on the excitation wavelength; but also the adsorbed biomolecules on the surface of synthesized Cu NPs, particle size, shape, and the ratio of reducing and capping agent which can enhance the emission peak and also, irradiation time as Gui et al [145] reported.…”
Section: Photoluminescence (Pl) Of Copper Nanoparticlesmentioning
confidence: 98%
“…In particular, metal NPs encapsulated within conductive MOFs create Schottky junctions at their interface, which act as active sites for analyte adsorption and charge transfer. 64 Similarly, metal nanoclusters composed of coinage metals (Cu, Ag, and Au) exhibit surface chemistry-dependent Please do not adjust margins photoluminescence 212,213 and can be linked together by rigid organic molecules to form MOFs with unique optical properties 214,215 Emission from powders of these materials has been used for gas sensing applications, 216,217 indicating that these MOFs would likely have utility as thin film sensors. In addition to improving sensor performance, integrating MOFs with other materials may improve material stability, an important consideration for sensor deployment.…”
Section: Composite Mof Materialsmentioning
confidence: 99%